Dampak positif dan negatif pembangunan di Komodo dan sekitarnya: sebuah tinjauan literatur - Syahadat, Ray March; Putra, Rizal Ichsan Syah (Environmental Science Program, Ivet University, 2021)
Background: As one of the world heritages by UNESCO and also the New 7 Wonders of Nature, Komodo National Park has become famous and in demand by both domestic and international visitors. The government then aggressively carried out development. This article was a literature review that aims to understand the impacts of development in Komodo and its surroundings. Methods: A total of 20 articles were selected from Google Scholar for analysis. Result: The results showed that the impact of development in Komodo and its surroundings can be seen from three dimensions, namely environmental, economic, and socio-cultural. Conclution: The impact of development in Komodo and its surroundings can be positive or negative. There are five recommendations for future research directions on the topic of development in Komodo. There are five recommendations for future research directions on the topic of development in Komodo.